MicroRNA and exosome profiling in multiple sclerosis. (April 2020) - Mycko, Marcin P; Baranzini, Sergio E
New DNA sequencing technologies have uncovered non-coding RNA (ncRNA) as a major player in regulating cellular processes and can no longer be dismissed as "junk" or "dark" RNA. Among the ncRNA, microRNA (miRNA) is arguably the most extensively characterized category and a number of studies have implicated them in regulating critical functions that can influence autoimmune demyelination. Of specific interest to multiple sclerosis (MS), miRNA have been implicated in both regulating immune responses and myelination, thus making them an attractive candidate for both pharmacological intervention and as disease biomarkers. In addition, exosomes, small vesicles secreted by most cell types and present in all body fluids, have been also shown to play roles in immune signaling, inflammation and angiogenesis. Therefore, exosomes are also being explored as tools for therapeutic delivery and as biomarkers. This article reviews the recent advances in miRNA and exosome profiling in MS and experimental models.